Encouraging employees' voice behavior through Islamic work ethics and civility climate: The role of organizational identification - Hendryadi Hendryadi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study explores the relationship between Islamic work ethics (IWE) and employee voice in the education sector. Our research model includes the role of civility climate and organizational identification as moderating factors. Using a time-lagged approach, we collected data from 227 lecturers across various universities and analyzed the model using a mediation moderation procedure and macro Process. Our results confirm that IWE is positively related to civility and employee voice. Moreover, employee voice is positively associated with the civility climate, which mediates IWE and employee voice. Lastly, the strength of the relationship between IWE and employee voice depends on the level of organizational identification.